PERSEPSI PETANI MELAKSANAKAN ALIH FUNGSI LAHAN PERTANIAN (Studi Kasus di Kecamatan Tarokan, Kabupaten Kediri, Jawa Timur) - Ardian Kardiono; Nugrahini Susantinah Wisnujati; Endang Siswati (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabay, 2023)
ABSTRACTThis study entitled Perceptions of Farmers Implementing Agricultural Land Conversion (Case Study: Tarokan District, Kediri Regency, East Java) aims to analyze farmers' perceptions of agricultural land conversion, and analyze factors that affect agricultural land conversion in Tarokan District, Kediri Regency. This method uses case studies, the research location is selected purposively. The data analysis used in this study is descriptive analysis to analyze farmers' perceptions and multiple linear regression data analysis using SMARTPLS software version 3 to analyze factors that influence farmers' perceptions to carry out land use conversion. Based on the results of the study, it was concluded that farmers' perceptions of agricultural land conversion in Tarokan District on average have a perception that they are still hesitant about airport development decisions, due to limited farmers' knowledge about the reasons and objectives of airport development. Multiple linear regression analysis obtained the results that the factors that influence the perception of farmers to carry out land use change, the factor that has a significant influence is the government while economic factors and social factors do not significantly affect the perception of farmers to carry out agricultural land conversionKeywords: Farmers perceptions, Land conversion, Economic Factors, Social Factors, Government.ABSTRAKPenelitian ini berjudul Persepsi Petani Melaksanakan Alih Fungsi Lahan Pertanian (Studi Kasus: Kecamatan Tarokan, Kabupaten Kediri, Jawa Timur) bertujuan untuk menganalisis persepsi petani terhadap alih fungsi lahan pertanian, dan menganalisis faktor-faktor yang mempengaruhi alih fungsi lahan pertanian di Kecamatan Tarokan Kabupaten Kediri. metode ini menggunakan studi kasus, lokasi penelitian dipilih secara purposive. Analisis data yang digunakan pada penelitian ini adalah analisis deskriptif untuk menganalisis persepsi petani dan analisis data regresi linier berganda menggunakan software SMARTPLS versi 3 untuk menganalisis faktor-faktor yang mempengaruhi persepsi petani untuk melaksanakan alih fungsi lahan. Berdasarkan hasil penelitian maka disimpulkan persepsi petani terhadap alih fungsi lahan pertanian di Kecamatan Tarokan rata-rata memiliki persepsi masih ragu-ragu terhadap keputusan pembangunan bandar udara, karena keterbatasan pengetahuan petani mengenai alasan dan tujuan pembangunan bandar udara tersebut. Analisis regresi linier berganda memperoleh hasil bahwa faktor-faktor yang mempengaruhi persepsi petani untuk melaksanakan alih fungsi lahan, faktor yang berpengaruh secara signifikan yaitu pemerintah sedangkan faktor ekonomi dan faktor sosial tidak berpengaruh secara signifikan terhadap persepsi petani untuk melaksanakan alih fungsi lahan pertanian.Kata Kunci: Persepsi Petani, Alih Fungsi Lahan, Faktor Ekonomi, Faktor Sosial, Pemerintah.